Low velocity impact response of basalt-aluminium fibre metal laminates. (15th May 2016) - Ferrante, L.; Sarasini, F.; Tirillò, J.; Lampani, L.; Valente, T.; Gaudenzi, P.
Abstract: This work reports on a preliminary study to assess the response of fibre metal laminates (FMLs) made of stacked layers of basalt fabric epoxy prepreg and aluminium sheets to low velocity impact and, through comparison with published results for Glare materials, benchmark their impact performance. Comparison is also made with results from plates of monolithic aluminium with comparable thickness. The effect of impactor size is also investigated whilst the impact energies were selected with the aim of inducing first crack (FC) and through the thickness crack (TTT) on the FML samples. Optical microscopy and profilometry were used to elucidate fracture mechanisms and the dent depth. The response of basalt fibre metal laminates was found to be both significantly influenced by the impactor size and fairly positive, proving to be competitive with monolithic aluminium plates although some issues about the aluminium/basalt interface have been raised. Graphical abstract: Highlights: Fibre metal laminates based on basalt fibres have been manufactured and their response to low velocity impacts assessed. FMLs showed a slightly higher level of first crack (FC) and through-the-thickness (TTT) crack threshold than monolithic Al. Impactor size significantly affected the impact response of FMLs. Composite-aluminium interfacial delaminations contributed to impact energy absorption. Aluminium/basalt interface needs to be optimized.